2016
DOI: 10.1186/s40064-016-3051-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of dietary supplementation of golden apple snail (Pomacea canaliculata) egg on survival, pigmentation and antioxidant activity of Blood parrot

Abstract: This study aims to evaluate the effects of supplementing golden apple snail (Pomacea canaliculata) eggs powder (EP) in the diet as a source of natural carotenoids on survival, pigmentation and antioxidant activity of Blood parrot. A total of 90 fish were divided into three treatment groups with three replicates per treatment. Blood parrot were fed with diets containing 0 (control), 5 % (EP 5 %), and 15 % (EP 15 %) dry powder of golden apple snail egg for 60 days, and nine fish per group were sampled at 20, 40,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The basal feed treatment obtained more non pigmented cells (Table 6). It was in line with Yang et al (2016) in blood parrot fish which showed xanthophores and erythrophores escalation when fed using Pomacea canaliculata eggs. Yang et al (2016) also stated that feed contained different kinds of carotenoids would generate colour differences.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The basal feed treatment obtained more non pigmented cells (Table 6). It was in line with Yang et al (2016) in blood parrot fish which showed xanthophores and erythrophores escalation when fed using Pomacea canaliculata eggs. Yang et al (2016) also stated that feed contained different kinds of carotenoids would generate colour differences.…”
Section: Discussionsupporting
confidence: 75%
“…It was in line with Yang et al (2016) in blood parrot fish which showed xanthophores and erythrophores escalation when fed using Pomacea canaliculata eggs. Yang et al (2016) also stated that feed contained different kinds of carotenoids would generate colour differences. The percentage of chromatophore showed that carotenoids addition affected the chromatophore appearance in the integument of Kurumoi rainbowfish.…”
Section: Discussionsupporting
confidence: 75%
“…and rami Boehmeria nivea obtained a 6:1 feed conversion and food acceptance may vary according to the mollusk' age. Pomacea can accumulate these pigments and convert them to astaxanthin only during the reproductive period as a way of protecting eggs and larval forms, as described by Yang et al (2016). Still, in the mentioned study, the greatest accumulation of astaxanthin (when added to the diet) was observed in the Pomacea's hepatopancreas.…”
Section: Resultsmentioning
confidence: 49%
“…According to Dreon et al (2004), the carotenoids of Pomacea eggs with proteins form a complex called ovorubin which is responsible for the protection against microsomal oxidation. Due to the properties of these eggs, studies have been directed to their use in fish feeding to enhance color in fancy carp (Cyprinus carpio) (BOONYAPAKDEE et al, 2015), parrots as an antioxidant and feather coloring (YANG et al, 2016), also to improve egg quality in Arabic chicken (NUSANTORO et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Upon publication of the original article (Yang et al 2016 ), it was noticed that the Acknowledgements section was incorrect. The Acknowledgements should actually read:…”
Section: Erratum To: Springerplus (2016) 5:1556 Doi 101186/s40064-01mentioning
confidence: 99%